Design of 2x2 Wide Bandwidth MIMO Antenna For LTE And 5G Sub-6GHz - Dian Rusdiyanto; Dian Widi Astuti; Muslim Muslim; Syah Alam; Yohanes Galih Adhiyoga (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
In this study, the design of a 2X2 MIMO microstrip antenna was proposed for LTE and 5G Sub-6GHz applications. The antenna is designed to have a wide bandwidth operating in the frequency range of 2300 MHz to 3600 MHz. The antenna material uses FR4 substrate which has a dielectric constant of 4.6 and a thickness of 1.6 mm. To achieve a wide bandwidth, the ground length is cut. Meanwhile, to achieve the resonant frequency using the square slot method on the radiator element. Antenna design begins with designing a single element shape, then designing a 2x2 MIMO antenna. The results of the MIMO2x2 antenna simulation show that the reflection coefficient and isolation coefficient of each antenna are below -10 dB. The results of the reflection coefficient of each antenna show that the bandwidth achieved is more than 2 GHz. At a frequency of 2300 MHz, the lowest gain is 2.98 dBi, while the highest gain is 3.10 dBi. The lowest and highest gains at a frequency of 3600 MHz are 3.83 dBi and 3.87 dBi. Overall, this antenna has achieved the desired goal, which is to have a wide bandwidth and be able to operate on LTE and 5G applications.